Rekomendasi Produk UMKM Kabupaten Malang menggunakan Metode Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) (Studi Kasus: Rumah Kreatif BUMN Telkom Kabupaten Malang) - Hafshah Durrotun Nasihah; Edy Santoso; Novanto Yudistira (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Malang Regency is one of the regency in East Java that has the largest population in Java, this causes the UMKM businessmen who are scattered in Malang Regency to be very numerous and varied. This study aimed to obtain UMKM product recommendations in Malang Regency which are registered in RKB Malang Regency. AHP and SAW are the methods of Decision Support System that were used to obtain UMKM product recommendations which compatible with the criteria weights that desired by the user. AHP method was used to calculate the weight of product criteria, meanwhile the SAW method was used to get the value of alternative product weights. The result of product's weighted alternative would be ranked from the largest to the smallest value, product with the largest weighted alternative value were the product that recommended by system based on the weighted criteria desired by the user. Based on the results of testing that using 7 cases testing accuracy testing that comparing the results of system with users,ait could be analyzed that the AHP and SAW methods were quite effective in getting product recommendations with an average value of 71,43%.